2012
DOI: 10.1097/aog.0b013e3182699259
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Bartholin Gland Cysts Identified on Pelvic Magnetic Resonance Imaging

Abstract: Objective To estimate the prevalence of Bartholin gland cysts in asymptomatic women serving as control participants who underwent pelvic magnetic resonance imaging (MRI) as part of research studies. The secondary aim was to investigate potential demographic characteristics associated with Bartholin gland cysts. Methods Pelvic MRIs from 430 control participants enrolled in five research projects were evaluated. All images were evaluated by at least two authors. The presence, laterality, and size of Bartholin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Cysts and abscesses of the Bartholin's gland are relatively common with a reported prevalence of between two and three in 100 women. 1 A cyst of the Bartholin's gland can form when the ducts become blocked due to trauma, mucus, or oedema secondary to infection. 2 Abscesses may form due to secondary infection of a cyst of the Bartholin's gland or less commonly due to primary infection of the Bartholin's gland itself and are generally due to polymicrobial infection of the retained cystic fluid by constituents of the vaginal flora, typically Escherichia coli or Staphylococcus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysts and abscesses of the Bartholin's gland are relatively common with a reported prevalence of between two and three in 100 women. 1 A cyst of the Bartholin's gland can form when the ducts become blocked due to trauma, mucus, or oedema secondary to infection. 2 Abscesses may form due to secondary infection of a cyst of the Bartholin's gland or less commonly due to primary infection of the Bartholin's gland itself and are generally due to polymicrobial infection of the retained cystic fluid by constituents of the vaginal flora, typically Escherichia coli or Staphylococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Cysts and abscesses of the Bartholin’s gland are relatively common with a reported prevalence of between two and three in 100 women . A cyst of the Bartholin’s gland can form when the ducts become blocked due to trauma, mucus, or oedema secondary to infection .…”
Section: Introductionmentioning
confidence: 99%
“…When the outflow path from the gland is blocked, a cyst forms. [1] The formation of a gland abscess is associated with secondary infection of the contents in the cyst or with the primary bacterial infection of the gland. Usually these are infections with a polymicrobial background.…”
Section: Introductionmentioning
confidence: 99%
“…The gland produce and secret mucus which is of alkaline pH and serves as a lubricant during sexual intercourse while it keeps the vulva moist [1] . They were first described by the Danish Anatomist, Casper Bartholin in the 17 th century [2] . Bartholin's gland cysts are the most common cystic enlargements of the vulva and are frequently benign than malignant.…”
Section: Introductionmentioning
confidence: 99%
“…Bartholin's gland cysts are the most common cystic enlargements of the vulva and are frequently benign than malignant. Approximately 2% -3% of women mostly in their reproductive age would develop Bartholin's gland cyst or abscess at some point in their life [2] , The abscesses is almost three times more common than the cysts [6,7] . It has been found that about 50% occur on the right labia, 42.9% on the left side, and 7.1% are bilateral [3] .…”
Section: Introductionmentioning
confidence: 99%